PENERAPAN MODEL PBL, NMM DAN PERMAINAN ULAR TANGGA DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR PADA MUATAN IPAS KELAS V SDN BENUA ANYAR 10 BANJARMASIN - Sayling Sansan Septemercy; Zain Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low levels of students’ critical thinking skills and learning outcomes, which were caused by one-way teaching and a lack of variety in instructional methods. The purpose of this study was to describe students’ critical thinking skills and learning outcomes. The research employed Classroom Action Research (CAR) over the course of three sessions, involving 15 fifth-grade students at SDN Benua Anyar 10 Banjarmasin. Data were collected through observation and tests. The results showed a significant improvement in each session: critical thinking skills increased from 33% in the first session to 87% in the third session, categorized as